The ruin of kings - Lyons, Jenn, 1970- (Tor, 2019)
When destiny calls, there's no fighting back. Kihrin grew up in the slums of Quur, a thief and a minstrel's son raised on tales of long-lost princes and magnificent quests. When he is claimed against his will as the missing son of a treasonous prince, Kihrin finds himself at the mercy of his new family's ruthless power plays and political ambitions. Practically a prisoner, Kihrin discovers that being a long-lost prince is nothing like what the storybooks promised. The storybooks have lied about a lot of other things, too: dragons, demons, gods, prophecies, and how the hero always wins. Then again, maybe he isn't the hero after all. For Kihrin is not destined to save the world. He's destined to destroy it.